EVALUASI KERAGAMAN KARAKTER FENOTIPE BEBERAPA VARIETAS KEDELAI (Glycine max L.) DI DAERAH ACEH UTARA - Nilahayati Nilahayati; Lollie Agustina P. Putri (Jurnal Floratek, 2015)
The diversity of phenotypic characters of several soybean varieties were evaluated in the area of North Aceh. The study was aimed at determining the phenotypic diversity of several varieties of soybean in North Aceh. The experiment was arranged in a non-factorial randomized complete block design. Varieties consisted of six varieties of soybean, namely Kipas Merah, Gamasugen 1, Muria, Mitani, Rajabasa dan Mutiara 1. Data were analyzed using analysis of variance and followed by Least Significant Difference Test. Results showed that variety exerted high significant effect on the characters of a number of branches, number of pods, number of seeds per plant, seed weight per plant, weight of 100 grains, and grain weight per plot, but did not significantly affect plant height at 2, 3, 4, 5 week after planting and height at harvest.  The highest heritability values was found at a weight of 100 seeds (0.95) and the lowest at plant height (0.28).  Mutiara 1 can be used as an alternative for farmers besides Kipas Merah, because Mutiara 1 produced a high yield and had the largest seed.